2007
DOI: 10.2193/2005-692
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Occurrence Models for Bat Species in California

Abstract: The ability to accurately predict the potential occurrence of species of management concern is useful for wildlife managers, particularly for those whose management activities involve large areas where sampling is difficult due to logistical or financial constraints. During the summers of 2002 and 2003, we used mist nets to capture bats (Myotis yumanensis, M. californicus, M. evotis, M. thysanodes, Eptesicus fuscus, Lasionycteris noctivagans, Tadarida brasiliensis, Antrozous pallidus, Lasiurus borealis, and La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Interpolation to new environments (Bahn and McGill 2007) can be achieved with the autologistic model if one utilizes a Gibbs sampling estimation and prediction method (Augustin et al 1996, Wintle andBardos 2006). Such improved prediction success has been found in subsequent studies using autocovariate approaches (Hoeting et al 2000, Osborne et al 2001, He et al 2003, Knapp et al 2003, Duff and Morrell 2007, McPherson and Jetz 2007. However, because such methods tend to be computer intensive, many studies that use autocovariates do not use the Gibbs sampler making it difficult to predict independent data (Betts et al 2006).…”
Section: Regression Prediction Versus Coefficient Estimationmentioning
confidence: 91%
“…Interpolation to new environments (Bahn and McGill 2007) can be achieved with the autologistic model if one utilizes a Gibbs sampling estimation and prediction method (Augustin et al 1996, Wintle andBardos 2006). Such improved prediction success has been found in subsequent studies using autocovariate approaches (Hoeting et al 2000, Osborne et al 2001, He et al 2003, Knapp et al 2003, Duff and Morrell 2007, McPherson and Jetz 2007. However, because such methods tend to be computer intensive, many studies that use autocovariates do not use the Gibbs sampler making it difficult to predict independent data (Betts et al 2006).…”
Section: Regression Prediction Versus Coefficient Estimationmentioning
confidence: 91%
“…Results of previous studies have generally concluded that landscape characteristics, such as amount of forest cover, proximity to water, and edge, influence bat occupancy or foraging activity (Duff and Morrell, 2007;Ford et al, 2006;Grindal and Brigham, 1999;Walsh and Harris, 1996;Yates and Muzika, 2006). However, extent of influence and relevant landscape features are species-specific.…”
Section: Introductionmentioning
confidence: 98%
“…Conducting foraging studies on bats is difficult because of their small size, vagility, and nocturnal nature (Duff and Morrell, 2007). Because radiotelemetry is expensive and logistically challenging, most studies examining habitat use by foraging bats rely on acoustic methods (Morris et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation structures and aerosphere variables model were developed using Akaike Information Criterion (AIC) following Duff & Morrell (2007), Ingersoll (2010) and Hoffman et al (2019) to evaluate and assemble models of vegetation structure and C. brachyotis abundance. The AIC was developed using the linear regression.…”
Section: Discussionmentioning
confidence: 99%